Energy Harvesting from Salinity Gradient - Muhthassim, B. (Institute of Physics Publishing, 2018)
Energy harvesting from salt water received attention started back in 1970s', but due to varying interests in the field and the growing potentials of other more promising sources, more work was required to fully establish it. This paper aims at identifying existing techniques of energy harvesting and the methodology involved determining an effective technique for small scale applications of the method. Capacitive deionization technique which involves electrochemical reaction was chosen for further analysis. The experiment was conducted to analyze factors affecting its performance including the electrode and the electrolyte. Combination electrode of carbon/aluminium, copper/aluminium and carbon/copper were selected and tested with different concentration of salty water. From the experiment, copper and aluminum electrodes were found to be the most effective among the rest. A DC-DC boost converter was used to step-up the voltage. Physical implementation of the circuit was done and the circuit was tested in which an input voltage of 1.022 V was boosted to 1.255 V. The efficiency of the boost converter was 38.17 based on input power and output power obtained. Â© 2018 Published under licence by IOP Publishing Ltd.